Fraksi Kloroform Ekstrak Buah Mentimun (Cucumis sativus L.) Sebagai Anti Bakteri terhadap Staphylococcus epidermidis - Viogenta, Pratika; Samsuar, Samsuar; Utama, Ahmad Ferry Yeriza (Politeknik Kesehatan Tanjungkarang, 2017)
The use of antibiotics in the community massively trigger resistance to bacteria, to that need for research on other alternatives, especially herbal medicine as an antibacterial. One of the medicinal plants are cucumbers that are widely available in Indonesia. The purpose of this study was to scientifically prove the antibacterial activity of chloroform fraction cucumber extract against Staphylococcus epidermidis. Extraction cucumber done by maceration, then extract fractionated with chloroform. The fraction was used the concentration of 5%, 10%, 15%, 20% and 25%. Then tested the antibacterial power and determination of the MIC. Results of test antibacterial of the extract chloroform of cucumber against S. epidermidis showed a zone of inhibition at concentrations of 5%, 10%, 15%, 20%, 25% diameter respectively 5.86 mm, 6.5 mm, 7.05 mm, 7.43 mm, and 9.92 mm, in addition to it tested the determination of minimum inhibitory concentration, minimum inhibitory concentrations of chloroform fraction extract cucumber fruit against S. epidermidis is at a concentration of 3%. The results obtained from the culture media growth on NA which means the fraction of the chloroform extract of cucumber in 3% is bacteriostatic.